The Implementation Of Unloading Agreements In The Port From Transportation Law Perspectives - Zahry Vandawati Chumaida (Yuridika, 2019)
Sea transportation is a commercial shipping business that is regulated in the provision of sea freight services where its business activities are very broad in its field and plays an important role in advancing trade both domestically or abroad including in its efforts to expedite the flow of goods from production areas to consumer areas. In the Port, there are tools to facilitate and facilitate the demolition and loading of goods from or to ships, or equipment to take fuel, water supplies and so on. In ports, of course, there are loading and unloading companies that are always connected with Indonesian ports (Pelindo). This is certainly related to the entry and exit of ships. The loading and unloading company is an Indonesian legal entity established to carry out and carry out business activities for loading and unloading goods from and to ships. In loading and unloading services, there are loading and unloading service providers, namely companies that carry out loading and unloading activities (stevedoring, receiving and receiving/delivery using loading and unloading labor) and loading and unloading equipment. obstacles or obstacles that might occur, these obstacles must be studied more deeply so that the impacts or losses that might be suffered by the parties in the vessel loading and unloading agreement can be minimized. The legal method used in answering the legal issues raised is through statute approach, conceptual approach, and case approach.